2019
DOI: 10.1038/s41598-019-55720-8
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopause as a key factor in the composition of the Endometrial Cancer Microbiome (ECbiome)

Abstract: Incidence rates for endometrial cancer (EC) are rising, particularly in postmenopausal and obese women. Previously, we showed that the uterine and vaginal microbiome distinguishes patients with EC from those without. Here, we sought to examine the impact of patient factors (such as menopause status, body mass index, and vaginal pH) in the microbiome in the absence of EC and how these might contribute to the microbiome signature in EC. We find that each factor independently alters the microbiome and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 49 publications
7
65
1
3
Order By: Relevance
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
“…The uterine microbiome of 'healthy' women was mostly investigated as a control group in studies of infertile women or those with a gynaecological pathology [7,8,11,[13][14][15][16][17][18][19][22][23][24] (Table 1). Nevertheless, these data suggest that commensal microorganisms can inhabit the upper reproductive tract of healthy women.…”
Section: Healthy Womenmentioning
confidence: 99%
See 3 more Smart Citations